Effective Advocacy Lessons from East Asia's Environmentalists - Haddad, Mary Alice (The MIT Press, 2021)
An examination of successful environmental advocacy strategies in East Asia that shows how advocacy can be effective under difficult conditions. The countries of East Asia-China, Japan, South Korea, and Taiwan-are home to some of the most active and effective environmental advocates in the world. And the governments of these countries have adopted a range of innovative policies to fight pollution and climate change: Japan leads the world in emissions standards, China has become the world's largest producer of photovoltaic panels, and Taiwan and South Korea have undertaken major green initiatives. In this book, Mary Alice Haddad examines the advocacy strategies that persuaded citizens, governments, and businesses of these countries to change their behavior. How did environmental activists succeed in countries that favor business interests and are generally hostile to citizen-based advocacy? Haddad identifies and describes, with examples, five of the most effective advocacy strategies used by environmentalists in East Asia: cultivate policy access, make it work locally, make it work for business, engage the heart, and think outside the box. Drawing on both qualitative and quantitative data, she develops the Connected Stakeholder Model to show how advocates work through personal and professional networks to influence people in power. Stakeholders involved in policymaking are connected to diverse and multiple networks, which help them to develop complex ideas about the policies they develop. East Asia's effective advocacy strategies, as well as Haddad's theoretical framework, offer valuable lessons for activists, policy makers, and researchers.